Strategi Konservasi Sumberdaya Air di Desa Regunung, Kecamatan Tengaran, Kabupaten Semarang - Sri Puatin; Munifatul Izzati; Sudarno Sudarno (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2014)
Title : The Strategy of Water Resources Conservation in Regunung Village, Tengaran Subdistrict, Semarang District. Water resource conservation is a required activity to do in in Regunung Village, Tengaran Subdistrict, Semarang District because this area is potentially dried and has often experienced the lack of clean water even though the water resource conservation is vegetatively conducted. The resecarh is conducted from June to August 2014. The purpose of this research is to analyze the strategy of water resource conservation in Regunung Village by analyze the social-economy condition and physical condition. The method used to gain data is obeservation and direct measuring including vegetation analysis, the data analysis of the citra condition of the changing of the land; the crossed tabulation analysis and Marcov Chain for the projection of the cahinging of the land use; the technique of interview using questioners to know the participation of community; the secondary data analysis, FGD to determine the strategy of water resource conservation with SWOT analysis. The population of this research is the people of Regunung Village. Respondent is purposively determined by the number of respondent based on Slovin formula, while the FGD informant is purposively determined. The result of the research shows that the condition of Regunung Village is located at discharged area CAT Salatiga with the various level of elevation and the type of soil is latosol. The changing of the use of land happening since 1991 - 2014. The vegetation condition shows that the planting method used in Regunung Village is Agroforestry. The index of diversity for three in Regunung Village is at the low level (0,8). The result of the social-economy condition research shows that the majority people's income is less than Rp. 1.000.000,00 and the level of participation is on placation level. The Water Resource Conservation Strategy suggested is the diversification strategy